Assortment of pumpkin (Cucurbita pepo L.) of Belarusian selection for the production of pumpkin oil - A. Ya. Khleborodov; I. M. Pochitskaya; O. S. Provotorova; P. A. Skripkovich (Овощи России, 2020)
Relevance and methods. Pumpkin fruits and seeds are valuable raw materials for the food and pharmaceutical industries. Of particular value are pumpkin seeds, from which oil and protein products are obtained. The purpose of our research is to identify the best breeding samples of pumpkin in terms of seed yield and pumpkin oil and to study their biochemical composition. The evaluation of 12 samples of pumpkin was carried out according to the main economic and biological characteristics. Results. According to the yield of seeds and the yield of pumpkin oil, the following samples were distinguished: Delta, Golosemyanno-kustovaya, Line 2-3, Line 2-5. The biochemical composition of seed samples with high seed yields was studied in terms of the content of proteins, fats, carbohydrates, amino acids, fatty acids, vitamins and minerals. A biochemical analysis of pumpkin seed oil for fatty acids, sterols and minerals was carried out. Seeds of hard-barked pumpkin of Belarusian selection are sources of high protein content (34-35%) with a wide range of essential amino acids, fats (43-45.8%), unsaturated and saturated fatty acids, as well as carbohydrates (9.6-11.9%) , a number of vitamins, macro- and microelements.